Seni Beluk: Context and Lyrics - Intan Noviati Manggala (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2018)
This article will examine one of Cianjur's local wisdoms, namely beluk art, its context and rumpaka. The data were obtained by descriptive analytical method,that is to examine and describe seni beluk qualitatively. Seni beluk is a type of art that is closely related to wawacan literature that uses pupuh rules. Commonly, seni beluk is performed at the 40 days old-baby birth ceremony, but gradually the pattern of life of society develops so that seni beluk is not only presented at the 40 days old-baby ceremony but also at a ceremonial event related with circumcision , wedding and religion ceremonials. Considering its presentation,  seni beluk still holds the tradition and culture the of ancestors.Keywords:beluk, local wisdom, lyrics